Data-Based Curriculum Evaluation and Teacher Performance: Quantitative Evidence of Strengthening Digital Systems in Learning Management - Fathurrochman, Irwan; Hamengkubuwono, Hamengkubuwono; Ramadani, M (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study investigates the influence of curriculum management practices on teacher performance in primary and secondary schools across Bengkulu Province, Indonesia. With the nationwide implementation of the Independent Curriculum (Kurikulum Merdeka) demanding stronger instructional quality, empirical evidence on how curriculum management contributes to teacher performance in local contexts remains limited. Methodology: A quantitative survey design was employed, involving 327 teachers selected through proportional stratified random sampling. Curriculum management was measured through three dimensions: planning, implementation, and evaluation. Teacher performance was assessed using indicators of pedagogical competence, instructional delivery, and classroom assessment practices. Data were analyzed using structural equation modeling (SEM). Main Findings: The findings reveal that curriculum management practices have a significant positive effect on teacher performance, with curriculum evaluation emerging as the strongest predictor. Novelty/Originality of this study: The study highlights the need for strengthening data-driven curriculum monitoring and professional development. These findings contribute to the literature on curriculum governance in developing regions by providing empirical evidence from a non-metropolitan Indonesian context. They also offer evidence-based recommendations for policymakers and school leaders in optimizing curriculum implementation within decentralized education systems.